BUSINESS ASSESSMENT THROUGH A FINANCIAL RATIO APPROACH AT DAWET IRENG & KUPAT TAHU “5758” JAMBI - Hamonangan, Samuel; Herlambang, Krisna; Permatasari, Mustika (Program Studi Hospitality dan Pariwisata, 2024)
Jambi City is a city in Jambi Province that has experienced an increase in culinary businesses such as restaurants, cafes, restaurants, and stalls. In managing a business, financial planning and analysis are needed to achieve smooth business. One of the analyses is the examination of financial statements. The type of research used by the author is descriptive research with a quantitative approach that collects data that is objective and measurable. The data collection techniques that the author uses are observation, interviews, documentation, bibliography and secondary data. The results showed that Return On Equity for 3 years measured by profit after tax divided by own capital obtained an average result of 1.72% or was in poor condition. The results of Return On Investment in the year from 2020 increased by 0.17% or with a value of 1.87% in 2021 and decreased in 2022 with a value of 1.59%. Cash Ratio or the restaurant's ability to pay off current debt with cash has not changed or remains at a value of 2.75%. Current Ratio which measures the restaurant's ability to pay off current debt if debt is collected reaches 27.5% or is at the lowest assessment score, Collection Period measures the restaurant's ability to collect receivables for 3 years is very good by obtaining a maximum assessment. Inventory Turn Over for the last 3 years has a maximum value of 5 which can be concluded that the effectiveness of inventory turnover in the restaurant is very good. Total Asset Turn Over has increased and decreased with an average calculation value of 2.69%. Own Ratio Capital to Total Assets during the study received a value of 4 or the effectiveness of using assets for business for 3 years of bookkeeping is not good. From the 8 aspects of assessing these financial ratios, Dawet Ireng & Kupat Tahu “5758” Jambi has an average financial performance that is less healthy from a score of ≤ 7 to > 66.5 obtaining an average value of 22.5 or less good and needs to be improved in the next period.